Pelatihan Pembuatan Konten Media Sosial Untuk Karang Taruna Sebagai Upaya Peningkatan Pengunjung Desa Agrowisata di Desa Bolu Seyegan - Sri Ngudi Wahyuni; Rum Muhammad Andri; Rahma Widyawati; Istiningsih Istiningsih; Anik Sri Widowati; Rosyidah Jayanti Vijaya (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2022)
Bolu Village is a village located in Seyegan District, Sleman Regency, Special Region of Yogyakarta Province. This village is developing an Agrotourism area as a financial improvement orientation. The use of technology in the form of social media branding is needed as an effort to promote the region. To introduce a new activity, service, or product, branding is an important step that needs to be done so that the wider community is interested in the object. This community service activity was carried out for 2 days involving 10 Karangtaruna members. By utilizing technology and owning a cell phone, this content creator training is able to provide insight for youth in an effort to increase visitors and increase finances. The evaluation results show that 20% of device ownership is still insufficient, and the rest is adequate. On average, all participants understand the basics of material in creating social media content and are able to implement it in the field. Approximately 90% of participants understand the material presented. This training is considered successful.